Cancer, inflammation and the AT1 and AT2 receptors - Smith Gary; Missailidis Sotiris (BMC, 2004)
Abstract The critical role of inappropriate inflammation is becoming accepted in many diseases that affect man, including cardiovascular diseases, inflammatory and autoimmune disorders, neurodegenerative conditions, infection and cancer. This review proposes that cancer up-regulates the angiotensin II type 1 (AT1) receptor through systemic oxidative stress and hypoxia mechanisms, thereby triggering chronic inflammatory processes to remodel surrounding tissue and subdue the immune system. Based on current literature and clinical studies on angiotensin receptor inhibitors, the paper concludes that blockade of the AT1 receptor in synergy with cancer vaccines and anti-inflammatory agents should offer a therapy to regress most, if not all, solid tumours. With regard to cancer being a systemic disease, an examination of supporting evidence for a systemic role of AT1 in relationship to inflammation in disease and injury is presented as a logical progression. The evidence suggests that regulation of the mutually antagonistic angiotensin II receptors (AT1 and AT2) is an essential process in the management of inflammation and wound recovery, and that it is an imbalance in the expression of these receptors that leads to disease. In consideration of cancer induced immune suppression, it is further postulated that the inflammation associated with bacterial and viral infections, is also an evolved means of immune suppression by these pathogens and that the damage caused, although incidental, leads to the symptoms of disease and, in some cases, death. It is anticipated that manipulation of the angiotensin system with existing anti-hypertensive drugs could provide a new approach to the treatment of many of the diseases that afflict mankind.